2017
DOI: 10.1007/s10461-017-1849-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Networks and HIV/STI Risk Behaviors Among Latino Immigrants in a New Receiving Environment

Abstract: The objectives of this study were to (1) describe the quantity and quality of social support networks of Latino immigrants living in a new receiving environment, and (2) to determine the role such networks play in their HIV/STI risk behaviors, including substance use. Double incentivized convenience sampling was used to collect egocentric social support network data on 144 Latino immigrants. Latent class analysis was used for data reduction and to identify items best suited to measure quality and quantity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
3
7
0
3
Order By: Relevance
“…The results on the psychosocial factors of social support, loneliness, and depressive symptoms provided some new findings. Participants with a self-reported HIV-antibody positive status reported less social support, which supports previous research indicating that social support is important for Hispanic MSM living with HIV infection (Althoff et al, 2017). In addition, social support may be important in preventing HIV infection among Hispanic MSM (Althoff et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results on the psychosocial factors of social support, loneliness, and depressive symptoms provided some new findings. Participants with a self-reported HIV-antibody positive status reported less social support, which supports previous research indicating that social support is important for Hispanic MSM living with HIV infection (Althoff et al, 2017). In addition, social support may be important in preventing HIV infection among Hispanic MSM (Althoff et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Participants with a self-reported HIV-antibody positive status reported less social support, which supports previous research indicating that social support is important for Hispanic MSM living with HIV infection (Althoff et al, 2017). In addition, social support may be important in preventing HIV infection among Hispanic MSM (Althoff et al, 2017). For Hispanic MSM living with HIV infection, social support has been shown to improve relationship dynamics, engagement in HIV care, and antiretroviral treatment adherence (Anderson et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Among adolescents, perceived support from friends was associated with lower sexual risk behaviors among female adolescents, while perceived support from family, not friends, was associated with lower sexual risk behaviors among male adolescents [44]. Lastly, in a study of Latino Immigrants in New Orleans [45], gender difference was not found in the association between social support and HIV risk behaviors in that social support served as a protective factor for both genders.…”
Section: Introductionmentioning
confidence: 99%
“…Classes cannot be measured directly; they are identified using a technique called latent class analysis [ 17 , 18 ], in which patterns of observable, categorical behaviors or measures (i.e., app usage patterns) are analyzed to classify members of a study population into unobservable subgroups. Latent class analysis has been used to characterize individuals in prior studies of eHealth interventions [ 19–23 ] and of PLWH [ 24–28 ]. Latent class analysis may be a valuable methodology to study multi-feature mHealth interventions such as PL that members choose to use differently based on underlying and unmeasurable traits.…”
Section: Introductionmentioning
confidence: 99%